2012
DOI: 10.1016/j.adolescence.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and racial socialization and self‐esteem of Asian adoptees: The mediating role of multiple identities

Abstract: Positive identity development during adolescence in general is a complex process and may pose additional challenges for adolescents adopted from a different culture. Using a web‐based survey design with a sample of 100 internationally adopted Asian adolescent and young adults, the present study examined the mediating role of multiple identities (i.e., ethnic, adoptive and interpersonal ego identities) in explaining the relationship between ethnic and racial socializations, ethnic neighborhood, and self‐esteem.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…Rivas-Drake et al, 2014). Similar results come from adoptive literature: some studies confirmed a positive influence of a strong ethnic identity on adopted adolescents and young adults' psychological well-being (Basow et al, 2008;Mohanty, 2013), while others found no significant differences in adjustment related to the degree of ethnic identity (Castle et al, 2011).…”
Section: Ethnic Identity and Self-esteem: The Moderating Effect Of Nasupporting
confidence: 84%
“…Rivas-Drake et al, 2014). Similar results come from adoptive literature: some studies confirmed a positive influence of a strong ethnic identity on adopted adolescents and young adults' psychological well-being (Basow et al, 2008;Mohanty, 2013), while others found no significant differences in adjustment related to the degree of ethnic identity (Castle et al, 2011).…”
Section: Ethnic Identity and Self-esteem: The Moderating Effect Of Nasupporting
confidence: 84%
“…In doing so, we develop a more comprehensive view of parenting approaches to add to the understanding of how parents engage in racial and ethnic socialization with transracially adopted children. In addition, although studies have typically focused on children adopted from a particular country (e.g., Kim, Reichwald, & Lee, ; Song & Lee, ) or limited their focus to a single ethnic or racial group (e.g., Butler‐Sweet, ; Crolley‐Simic & Vonk, 2011; Mohanty, ; Samuels, ), we included parents who have adopted Latino, Black, and biracial children domestically, as well as parents with children from Africa, the Caribbean, Latin American, and Asian countries to expand understanding of how socialization strategies that parents use vary by the racial or ethnic background of the child.…”
Section: Background On Transracial Adoptionmentioning
confidence: 99%
“…Related research findings suggest that the promotive effect of ethnic socialization on youth outcomes is mediated by a strong ethnic identity (Gartner, Kiang, & Supple, 2014;Mohanty, 2013;Umaña-Taylor et al, 2014). They also highlight the promotive benefit of ethnic identity that provides youth with confidence and a positive self-concept, which contribute to improved school achievement and life satisfaction.…”
Section: Theoretical Frameworkmentioning
confidence: 99%